Leute machen Kleider: Ein Arbeitskampf indonesischer Textilarbeiterinnen zwischen Selbstorganisation und gewerkschaftlicher Organisierung - Engelhorn, Anja (Verlag Barbara Budrich, 2023)
This empirical study analyses a labour conflict of Indonesian textile workers in the north of Jakarta that lasted several years. From the blockade of the factory to the appropriation of the factory to self-managed production, the different perspectives of the actors involved are elaborated. This is discussed along the lines of a feminist concept of labour struggle, which was theoretically elaborated in the case.